2020
DOI: 10.1038/s41598-020-70499-9
|View full text |Cite
|
Sign up to set email alerts
|

Menthol can be safely applied to improve thermal perception during physical exercise: a meta-analysis of randomized controlled trials

Abstract: Menthol is often used as a cold-mimicking substance to allegedly enhance performance during physical activity, however menthol-induced activation of cold-defence responses during exercise can intensify heat accumulation in the body. This meta-analysis aimed at studying the effects of menthol on thermal perception and thermophysiological homeostasis during exercise. pubMed, EMBASE, Cochrane Library, and Google Scholar databases were searched until May 2020. Menthol caused cooler thermal sensation by weighted me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 58 publications
3
9
0
Order By: Relevance
“…Physical cooling seems more effective than perceptional cooling in improving physiological parameters and physical performance when comparing cooling strategies. In agreement with another meta-analysis (Keringer et al, 2020), we found no effects of perceptional cooling on physiological outcomes, as menthol is a non-thermal cooling stimulus that acts on thermoreceptors, inducing sensations of coolness without physical reductions in body temperature (Watson et al, 1978). We further found no effects of menthol cooling on performance, which is in line with two previous (Douzi et al, 2019;Keringer et al, 2020) but in contrast with one meta-analysis (Jeffries and Waldron, 2019).…”
Section: Figure 13supporting
confidence: 92%
“…Physical cooling seems more effective than perceptional cooling in improving physiological parameters and physical performance when comparing cooling strategies. In agreement with another meta-analysis (Keringer et al, 2020), we found no effects of perceptional cooling on physiological outcomes, as menthol is a non-thermal cooling stimulus that acts on thermoreceptors, inducing sensations of coolness without physical reductions in body temperature (Watson et al, 1978). We further found no effects of menthol cooling on performance, which is in line with two previous (Douzi et al, 2019;Keringer et al, 2020) but in contrast with one meta-analysis (Jeffries and Waldron, 2019).…”
Section: Figure 13supporting
confidence: 92%
“…Almost all studies conducted with oral menthol have opted for a per-cooling strategy, which seems more suited to its mode of action. As the proposed mechanism of action of internally applied menthol targets thermal sensation, improved thermal comfort, and rate of perceived exertion ( 15 , 150 ), the ergogenic effect is more likely to occur with the higher thermal stress obtained in more advanced stages of exercise. Accordingly, menthol seems to benefit performance when given in several successive internal administrations throughout exercise ( 100 , 101 , 108 , 110 , 111 , 128 , 129 ) or even as a single dose in the latter stages of exercise ( 116 ).…”
Section: Discussionmentioning
confidence: 99%
“…As in our previous meta-analysis of sepsis 20 , publications reporting immunosuppressive conditions (e.g., transplantation, HIV infection) were not included in the current analysis. Similarly to our past studies 20 , 21 , the search was conducted separately by two authors (JT, AG), who also assessed study eligibility and extracted data from the selected studies independently. Disagreements were resolved by consensus, with the help of a third party (ZR).…”
Section: Methodsmentioning
confidence: 99%